2017
DOI: 10.1177/1934578x1701201218
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of 1’-Hydroxyethylnaphthazarins and their Derivatives

Abstract: The ABTS  radical cation scavenging activity of known (2-5, 9, 10) and new (6-8) 1'-hydroxyethylnaphthazarins and their products of esterification and etherification was evaluated and a structure-activity relationship was studied. It was shown, that the structure of side chains does not affect the radical scavenging activity of 1'-hydroxyethylnaphthazarins and their derivatives. The presence of methoxyl groups on the naphthazarin core slightly enhanced the antioxidant activity of compounds compared with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It was reported that highest yield was obtained at higher temperature and lower flow rates ( Akgun, Erkucuk, Pilavtepe, & Yesil-Celiktas, 2011 ). Subsequently, the ultrasonication technique was also exploited to primarily obtain deoxyshikonin and other naphthoqimone derivatives from the residual extract of Lomandra hastilis ( Park et al, 2017 , Utkina & Pokhilo, 2017 ). On the similar lines, L. erythrorhizon extract was subjected to sonication to obtain acetylshikonin, shikonin, deoxyshikonin, β-sitosterol and β,β-dimethylacrylshikonin ( Li, Xu, Zhu, & Wang, 2012 ).…”
Section: Isolation and Analytical Aspects Of A/s And Their Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that highest yield was obtained at higher temperature and lower flow rates ( Akgun, Erkucuk, Pilavtepe, & Yesil-Celiktas, 2011 ). Subsequently, the ultrasonication technique was also exploited to primarily obtain deoxyshikonin and other naphthoqimone derivatives from the residual extract of Lomandra hastilis ( Park et al, 2017 , Utkina & Pokhilo, 2017 ). On the similar lines, L. erythrorhizon extract was subjected to sonication to obtain acetylshikonin, shikonin, deoxyshikonin, β-sitosterol and β,β-dimethylacrylshikonin ( Li, Xu, Zhu, & Wang, 2012 ).…”
Section: Isolation and Analytical Aspects Of A/s And Their Derivativesmentioning
confidence: 99%
“… Sut et al, 2017 Alkanna strigosa Soxhlet extraction (CHCl 3 : MeOH: H 2 O) (5:4:1) Preparative tlc Alkannin and shikonin Aburjai, Al-Janabi, Al-Mamoori, & Azzam, 2019 Echium italicum Maceration Hexane-Etilacetae silica gel column chromatography 2-Methyl- n -butyrylshikonin, isovalerylshikonin, acetylshikonin and deoxyshikonin Eruygur, Yılmaz, Kutsal, Yücel, & Üstün, 2016 Lomandra hastilis Sonication n -hexane–acetone (3:1) Preparative TLC 5,8-Dihydroxy-2-ethyl-3,6,7-trimethoxy-1,4- naphthoquinone, lomazarin, 2-(1′- acetoxyethyl)-5,8-dihydroxy-3,6,7-trimethoxy-1,4-naphthoquinone, 5,8-dihydroxy-3,6,7-trimethoxy-2-(1′-methoxyethyl)-1,4- naphthoquinone, isonorlomazarin, 5,8- dihydroxy-2-(1′-hydroxyethyl)-1,4-naphthoquinone, 2-(1′- acetoxyethyl)-5,8-dihydroxy-1,4-naphthoquinone, 5,6,8- trihydroxy-2-ethyl-3,7-dimethoxy-1,4-naphthoquinone and ethylmompain dimethyl ether. Utkina & Pokhilo, 2017 Alkanna tinctoria Extraction with 95% EtOH Hexane–EtOAc (20:1–0:1, volume percentage) Methanol Hexane–EtOAc (5:1– 4:1, volume percentage) Silica gel column chromatography Sephadex column Reverse phase column chromatography Angelylalkannin, 5-methoxy angenyalkannin, alkanfuranol, alkandiol, acetylalkannin and dimethylacrylshikonin. Tung, Du, Yuan, Shoyama, & Wang, 2013 supercritical CO 2 extraction 0.025% aqueous TFA and acetonitrile HPLC-PDA analysis Alkannin/shikonin Akgun, Erkucuk, Pilavtepe, & Yesil-Celiktas, 2011 Echium italicum Solid–liquid extraction MeOH:HCOOH (20:1, volume percentage) and THF:MeCN:H 2 O:HCOOH (30:20:50:0.5, volume percentage) Chiral thin-layer chromatography and semi-preparative HPLC Angelylshikonin, 2-methyl- n -butyrylshikonin, and isovaleryl shikonin Albreht, Vovk, Simonovska, & Srbinoska, 2009 Arnebia nobilis Reichb.f.…”
Section: Isolation and Analytical Aspects Of A/s And Their Derivativesmentioning
confidence: 99%
“…4 It is well known that an antiradical activity is the most common property of naphthazarin pigments and their derivatives. 1,[5][6][7] In continuation of our study of structure-antiradical activity relationships of naphthazarin pigments and their derivatives, we also evaluated ABTS •+ scavenging activity of naphthazarin-carbohydrate conjugates to clarify the effect of a sugar fragment on the activity. The antiradical activity of naphthazarin-carbohydrate nonglycoside conjugates is studied for the first time.…”
mentioning
confidence: 99%
“…The first group—the naphthazarin-carbohydrate conjugates 4 and 5 derived from the methyl ether of naphthopurpurin ( 1 ), the second group—the conjugates 6-9 derived from the dimethyl ether of ethylmompain ( 2 ), and the third group—the conjugates 10-12 derived from the dimethyl ether of ethylisomompain ( 3 ). Compounds 1-4 , 6-8 we synthesized early, 2,46 compounds 5 , 9-12 were synthesized for the first time. The chemical structures of the synthesized compounds were confirmed by IR spectroscopy, 1 H, and 13 C NMR spectroscopic data including 2D HMBC data and mass spectrometry.…”
mentioning
confidence: 99%